Impact of aquaculture field school on community fish farming - De, Himansu Kumar; Radheyshyam, .; Saha, Gour Sundar; Safui, Lekha; Chandra, Suresh; Adhikary, Subhendu; Barik, Nagesh Kumar; E. Eknath, Ambekar (Indian Journal of Fisheries, 2016)
Community based aquaculture, a subset of the rural aquaculture, is characterised with low fish production level. Sustainable improvement of productivity levels in such resources has remained a challenge. The study adopted a novel approach of technology transfer through aquaculture field school which involves provision of technical advices and no physical inputs. The article tries to capture its impact on fish production levels and economics of community based aquaculture. The study was conducted during 2009-2012 in Khurda and Puri districts of Odisha by surveying randomly selected farmers of community ponds. Demonstration, need-based skill training, field days, workshops and field visits were organised periodically for fish farmers involved in community based aquaculture management. In order to study the impact of technical inputs, data were collected from 31 randomly selected village community ponds. Farmers provided with technical advices could improve pond management practices significantly (p<0.05). This included eradication of aquatic weeds, removal of weeds and predatory fishes, enhancing pond productivity, stocking fingerlings and/or yearlings, partially feeding fish with locally available feed. This has resulted in better fish production (@ 2192 kg ha-1yr-1) than pre-project period (@1081 kg ha-1yr-1). Motivational drive, need based technical advice and follow up action brought behavioral change in fish farmers for higher investment for intensification of pond management. Average expenditure in community based aquaculture rose significantly (p<0.05) from `40146 ha-1yr-1 to `87071 ha-1yr-1. Average net returns from community ponds at the end of the project period increased to `95068 ha-1 yr-1 against `34057 ha-1yr-1.